2007
DOI: 10.2215/cjn.03921106
|View full text |Cite
|
Sign up to set email alerts
|

Nephrogenic Systemic Fibrosis

Abstract: Nephrogenic systemic fibrosis (NSF) is a devastating complication of severe renal failure. Recent reports suggest that exposure to gadolinium-containing contrast agents (GCCA) is associated with the occurrence of NSF. The population of patients with ESRD in and around Bridgeport, CT, was studied during an 18-mo period. The incidence of NSF was 4.3 cases per 1000 patient-years. Each radiologic study using gadolinium presented a 2.4% risk for NSF. The association between gadolinium exposure and NSF was highly si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
152
1
7

Year Published

2007
2007
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 235 publications
(162 citation statements)
references
References 20 publications
2
152
1
7
Order By: Relevance
“…To date, it has only been reported in patients with severely impaired renal function (SIRF), endstage renal disease (ESRD), and those in acute renal failure (ARF) (2)(3)(4)(5). The many other risk factors thought to be associated with NSF include: edema (6), metabolic acidosis, thrombotic events, high-dose erythropoietin (EPO) (7,8), systemic inflammation (9), recent surgery, kidney disease (10), and gadolinium (Gd 3þ )-based contrast agent (GBCA) exposure (11,12), especially when used at relatively high dose GBCA (5,13).…”
mentioning
confidence: 99%
“…To date, it has only been reported in patients with severely impaired renal function (SIRF), endstage renal disease (ESRD), and those in acute renal failure (ARF) (2)(3)(4)(5). The many other risk factors thought to be associated with NSF include: edema (6), metabolic acidosis, thrombotic events, high-dose erythropoietin (EPO) (7,8), systemic inflammation (9), recent surgery, kidney disease (10), and gadolinium (Gd 3þ )-based contrast agent (GBCA) exposure (11,12), especially when used at relatively high dose GBCA (5,13).…”
mentioning
confidence: 99%
“…Although we applaud the efforts of the investigators to elucidate information about this potentially devastating condition, we encourage caution in using the clinical scoring system they describe to define nephrogenic systemic fibrosis (NSF). Although there have been few systematic investigations to date, it is worthwhile to note that in the study by Todd and colleagues, the reported 13% prevalence of NSF among dialysis patients is much higher than that observed in 2 other investigations (2,3). A study from Scotland used skin biopsy, full clinical examination, and laboratory data to establish the diagnosis of NSF, and the reported prevalence among a cohort of 1,826 dialysis patients was 0.77% (2).…”
Section: To the Editormentioning
confidence: 90%
“…A study from Scotland used skin biopsy, full clinical examination, and laboratory data to establish the diagnosis of NSF, and the reported prevalence among a cohort of 1,826 dialysis patients was 0.77% (2). Similarly, a study of hemodialysis patients in Connecticut identified 3 (0.64%) of 467 dialysis patients as having NSF, based on clinical examination and skin biopsy (3). We suggest that the substantial difference in the prevalence of NSF reported by Todd et al compared with that observed in other available studies, as well as the potentially low specificity of their clinical criteria for NSF, combine to make the reported prevalence of 13% an overestimate.…”
Section: To the Editormentioning
confidence: 99%
“…In a retrospective population-based study in nine urban and suburban communities of Connecticut (January 2005 to June 2006) the absolute risk for development of NSF was 3.4% when a patient with ESRD received Gd-CA (three of 87 patients; two patients received gadodiamide, one patient gadopentetate). No cases of NSF occurred without Gd-CA exposure (n ¼ 380) (29). In a retrospective review of the medical charts from two hospitals in New York (January 1997 to June 2007), 15 patients developed NSF.…”
Section: Epidemiologymentioning
confidence: 99%
“…Therefore, variations in prevalence and incidence of NSF are not surprising. Nevertheless, the studies provide important insight to estimate the risk of NSF: a) patients who did not receive Gd-CA and/or have a normal renal function have virtually no risk to develop NSF (29). b) patients receiving a standard Gd-CA dose have a lower risk to develop NSF compared to patients receiving a high single dose or multiple doses (28,30).…”
Section: Epidemiologymentioning
confidence: 99%